Exploration of E-portfolio IC2 Innovative Management Model to Promote the Professional Development of University Teachers (Global Journal of Human-Social Science, 2012)
As a developmental evaluation tool and a personalized learning platform E-portfolio shows great prospects in the professional development of university teachers By drawing on the innovative service model of IC in university libraries this article aims to explore an innovative management model of IC and apply it in the establishment and use of E-portfolio so as to tamp the theoretical foundation of E-portfolio by means of which we can maximize the function of Eportfolio get our knowledge shared and innovated and thus promote the professional development of university teachers
Keywords: E-portfolio; IC² innovative management model; profession development Introduction